Neuromuscular impairment of knee stabilizer muscles in a COVID-19 cluster of female volleyball players: which role for rehabilitation in the post-COVID-19 return-to-play? - de Sire, A.; Demeco, A.; Marotta, N.; Spanò, R.; Curci, C.; Farì, G.; Fortunato, F.; Iona, T.; Lippi, L.; Paolucci, T.; Invernizzi, M.; Ammendolia, A. (Applied Sciences, 2022)
COVID-19 athletes reported persistent and residual symptoms many weeks after initial infection, including cough, fatigue, and neuromuscular disorders. Poor neuromuscular control may cause inefficient movement strategies increasing anterior cruciate ligament load. This is particularly relevant in female athletes, who show a 3-time higher risk than male counterparts. Aim is to evaluate the impairment in thigh muscles activation, body composition, and physical performance after COVID-19 in volleyball athletes. We recruited a cohort of female professional players from the same team. We assessed the pre-activation time of Rectus Femoris (RF), Vastus Medialis (VM), Medial Hamstring (MH), and Lateral Hamstring (LH) before (T0) and after (T1) COVID-19 infection, bioelectrical impedance analysis (BIA), and jump tests. We included 12 athletes with COVID-19 infection diagnosis in January 2021. At T1 we found a significant (p < 0.05) delay (ms) of the activation time of RF (426 ± 188 vs. 152 ± 106); VM (363 ± 192 vs. 140 ± 96); BF (229 ± 60 vs. 150 ± 63); MH (231 ± 88 vs. 203 ± 89), and a significant reduction of body composition at BIA. The neuromotor imbalance of the knee stabilizer muscle in female athletes after COVID-19 infection determines a deficit of knee stabilization. Physicians should consider neuromuscular and metabolic sequelae to identify athletes at higher risk of injury and set up specific neuromuscular rehabilitation protocols.